Winnipeg's Pediatric Cardiac Inquest: The Ethical Issues - Hinam, Irene (Operating Room Nurses Association of Canada Journal, 1999)
I will begin my case presentation by telling my story and then describing some of the ethical issues that challenged those of us most intimately involved with the Cardiac Surgical Program at Children’s Hospital, HSC, Winnipeg, Manitoba in 1994.